The Study of Culture and its Models - Genzelis, Bronislovas (Problemos, 1984)
An attempt is made to attract attention to the difficulties which one faces while studying culture. Culture is studied using scientific methods. The possibilities of science as a phenomenon of culture in its turn are related to a particular level of culture. So a researcher is constrained to proceed from the models of the object under discussion constructed by himself or adopted from others. However, a model of reality and reality itself do not coincide. In addition, a researcher is a product of a particular time. This dependency necessarily modifies his style of thinking and cognitive possibilities and limits his sphere of action to the definite empirical data and the present theoretical conceptions.